Uso de agregados reciclados y fibra de acero para elaborar un concreto satisfactorio a flexión en vigas - Avila Domínguez, Vanessa Alexandra (2018)
Concrete is one of the most used materials in the construction industry; and at the same time, it is the one that generates more waste at present, that is why it has being tried to reuse the mentioned material by manufacturing recycled concrete. The objective of this research was to create some concrete material by using recycled aggregates that demonstrate comparable resistance levels to regular ones. From the construction and metallurgical industry, recycled aggregates were obtained such as: brick dust, foundry sand and coarse aggregate particles after tested concrete samples. The design of the dosage of the recycled concrete (CR) was made by considering the workability of the mixture and its resistance to compression, traction and bending. To improve the mechanical behavior against flexural loads of the CR, 4D Dramix, steel fibers were incorporated into the mixture. The mechanical properties of recycled concrete and recycled concrete are the results of reinforcing with steel fibers (CR + F) which were compared with those obtained by testing samples of normal concrete (CN); and it was observed that the CR samples had a significant improvement in the resistance in compression with respect to the CN samples. On the other hand, the tensile and flexural resistances in the CR + F samples were significantly higher than those obtained by testing CN samples.